Model Pengembangan Interpretasi Pariwisata Edukasi di Museum Kota Makassar - Junaid, Ilham; Ilham, Muhammad Dzakwan Mufadhdhal; Saharuna, Muhammad Yusuf (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
This study aims to describe the form of interpretation implemented at the Makassar city museum and analyze the efforts to implement the museum as an educational tourist attraction through the concept of interpretation. This study applies a qualitative methodology at the Makassar city museum in the April˗May 2022 period. The results showed that the Makassar city museum staff had implemented personal and nonpersonal interpretations in supporting the museum’s function as historical and cultural preservation and an educational tourist attraction. However, museum staff consider several aspects required for the practice of interpretation. For example, visitors exploring the collection without being guided by museum staff can reduce the quality of the tourist experience. Museum staff should also evaluate issues such as museum collections that do not have information labels and labels that are too short and unclear and do not use international language. This study proposes five models of interpretation development, i.e., a digital-based information management model (website and social media); models of strengthening cooperation and partnerships; nonpersonal interpretation identification and evaluation model; model of integration of personal and nonpersonal interpretation; and collaboration and partnership models. This research enhances the urgency of interpretation in supporting education-based tourism. The museum offers an experience for visitors to see cultural artifacts of historical value and carry out educational activities and experiential learning while travelling.